Corrections to herbarium citation of the type specimens of two Chinese flowering plants recently published in Phytotaxa - He, Luo-Shu; He, Hai (Phytotaxa, 2017)
The herbarium citation of the type specimens of both Clematis wuxiensis Q.Q.Jiang & H.P.Deng (Ranunculaceae) and Impatiens shennongensis Q.Wang & H.P.Deng (Balsaminaceae) recently published in Phytotaxa is corrected from SWU to SWCTU.